2020
DOI: 10.1016/j.psj.2019.12.069
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: Association of temporal expression of myostatin with hypertrophic muscle growth in different Japanese quail lines

Abstract: Myostatin ( MSTN ) negatively regulates in muscle growth and development. Among alternative splicing isoforms of avian MSTN, MSTN-A has antimyogenic activities and MSTN-B functions as a promyogenic factor. In this study, different lines of Japanese quail were used: a random bred control ( RBC ) and a heavy weight ( HW ) quail line with muscle hypertrophy. The objectives of the current study are to compare temporal expression of the MSTN isofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Heavy-weight (HW) and low-weight (LW) quail lines have been developed by selectively breeding of more than 80 generations for body weight [ 17 ]. The HW quail line showed muscle hypertrophy with a higher ratio of Mstn-B / Mstn-A forms, and the LW line showed hypoplasia with a lower ratio of Mstn-B / Mstn-A forms [ 8 , 18 ]. In addition, overexpression of the MSTN-B form in transgenic quail increased muscle mass [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heavy-weight (HW) and low-weight (LW) quail lines have been developed by selectively breeding of more than 80 generations for body weight [ 17 ]. The HW quail line showed muscle hypertrophy with a higher ratio of Mstn-B / Mstn-A forms, and the LW line showed hypoplasia with a lower ratio of Mstn-B / Mstn-A forms [ 8 , 18 ]. In addition, overexpression of the MSTN-B form in transgenic quail increased muscle mass [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, myostatin is a negative regulator in muscle development, and animals with the myostatin mutation produce more muscle mass [ 4 ]. Currently, an effective breeding method is selecting myostatin-mutant individuals to propagate high-performance offspring in Bos taurus and Coturnix japonica [ 4 , 5 , 6 ]. During the selection of 11 generations for AFP (abdominal fat percentage), the fat chicken line and lean chicken line were produced from the same ancestors, and Wang et al found that the level of AFP was 5.29 times higher in the fat chicken line than in the lean one [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that differential expression of Mstn may potentially contribute to embryonic muscle development when the myofiber is being formed, thereby influencing rates of muscle growth at posthatch ages. This explanation is partially supported by the recent findings of the involvement of Mstn in regulation of total myofiber numbers in chickens and quail with CRISPR/Cas-mediated indel mutations or shRNA-mediated knockdown of the Mstn gene (Bhattacharya et al., 2019; Kim et al., 2020a ; Lee et al., 2020 ).…”
Section: Resultsmentioning
confidence: 72%
“…Among alternative mRNA splicing variants ( Mstn-A to Mstn-E ) in avian Mstn , Mstn-A , a dominant form, had an inhibitory effect on proliferation of quail myogenic cells, fusion rate, and myotube formation in vitro ( Shin et al., 2015 ). Our recent study showed that the heavy-weight quail line ( HW ) had a muscle hypertrophic phenotype with low expression levels of Mstn in E14 compared with the CON ( Kim et al., 2020a ). Opposite of the antimyogenic function of Mstn-A , the Mstn-B form has promyogenic function ( Shin et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation